FEATURES OF COMBATING CRIMES IN THE BANKING SECTOR IN THE RUSSIAN FEDERATION AND IN CHINA - Garmaev, Yury Petrovich (European Scientific Journal, ESJ, 2014)
The author believes that global macroeconomic changes, such asdecreasing prices for oil and gas, should not be considered as a major threatto the banking system of Russia. The first place there takes the threat ofcrime and corruption. It seems appropriate to study the experience ofcounteracting the economic, including banking, crime, gathered in China -the state which is in many aspects very similar to the Russian Federation.